1997
DOI: 10.1046/j.1469-0705.1997.10010066.x
|View full text |Cite
|
Sign up to set email alerts
|

Sonodynamic changes after transcatheter arterial embolization in a vaginal hemangioma: case report

Abstract: A 36-year-old pregnant woman with a rapidly growing hemangioma in the vagina was treated by transcatheter arterial embolization after delivery. Blood flow characteristics within the tumor were evaluated using transvaginal color Doppler ultrasound both before and after the embolization. The vascular resistance in the tumor vessels within the vaginal hemangioma was observed to be significantly decreased; the tumor reduced in volume following this non-surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Selective embolisation sometimes has to be carried out through two or more steps to avoid or reduce risks of complications, primarily acute ischaemia caused by occlusion of important anomalous arteries 10. Besides our case, we found two other case reports showing good results after embolisation of vulvar arterio-venous malformation by using a coil 11 12…”
Section: Discussionmentioning
confidence: 51%
“…Selective embolisation sometimes has to be carried out through two or more steps to avoid or reduce risks of complications, primarily acute ischaemia caused by occlusion of important anomalous arteries 10. Besides our case, we found two other case reports showing good results after embolisation of vulvar arterio-venous malformation by using a coil 11 12…”
Section: Discussionmentioning
confidence: 51%
“…A literature search revealed that a surgical excision remains the curative treatment in most cases, and conservative therapy, such as sclerosing agents, cryotherapy, carbon dioxide laser and LEEP, may alternatively be used [5]. Transcatheter arterial embolisation, after delivery, has been reported in the treatment of rapidly growing vaginal haemangioma [11]. Although hysterectomy, as a primary mode of therapy for cases of haemangioma of the cervix presenting with vaginal bleeding, has been reported by Powell et al, most were performed because the lesion was suspected to be malignant [12].…”
Section: Discussionmentioning
confidence: 99%
“…When symptomatic, they manifest with symptoms related to mass effect [93,97] or abnormal vaginal bleeding in females [96]. During pregnancy, hemangiomas may grow rapidly, increasing the risk of bleeding, especially during delivery, and may necessitate caesarian section [96][97][98].…”
Section: Genital Hemangiomamentioning
confidence: 99%
“…Sonographic findings are nonspecific and may reveal a complex mass with echogenic, shadowing foci corresponding to phleboliths [99]. Intralesional vascularity on Doppler sonography with low-resistance flow can be seen [98,99]. CT characteristics include a mass with lobulated margins and phleboliths.…”
Section: Genital Hemangiomamentioning
confidence: 99%